Objects and frontiers in modern Asia
1 online resource.
Keywords: "Focusing on the geographies between the Mekong and the Indus, this book brings objects to the centre of enquiry in the understanding of modern Asian frontiers. It explores how a range of objects has historically been significant bearers and agents of frontier making. For instance, how are objects connected to aspects of state making, social change, everyday life, diplomacy, political and ecological worlds, capital, forms of violence, resistances, circulations, and aesthetic expressions? The book seeks to interrogate and understand the dynamism of frontiers from the vantage point of objects such as salt, rubber, tea, guns, silk scarves, horses, and opium. It attempts to explore objects as sites of encounter, mediation or dislocation between the social and the spatial. The book not only locates objects in the specificities of frontier spaces, but it also looks at how they are produced, circulated and come to be intricately linked to a wide range of people, institutions, networks and geographies. In the process, it explores how objects traverse and come to inhabit multiple historical, cultural and geographical scales. This book will be of interest to researchers and academics working in areas of history, social and cultural anthropology, Asian studies, frontiers and borderland studies, cultural studies, political and economic studies, and museum studies"--